PENGUJIAN PECKING ORDER THEORY DALAM STRUKTUR MODAL PADA INDUSTRI PERBANKAN INDONESIA (Studi Kasus pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2011-2015) - Lita, Lita Doneka Saseselia Tambunan B1021131099 (Jurnal Manajemen Update, 2017)
ABSTRACTThis study aims to test the application pecking order theory in capital structure in the banking companies listed in the Indonesia stock exchange period 2011-2015 and analyze to analyze the effect of Â profitability, asset structure and growth. Firm size is used as a variable that moderates the relationship between independent variables to capital struktur. The data used is secondary data obtained through the official web stock exchange in www.idx.co.id . the number of samples used for research is 75 data. Sampling technique using purposive sampling, then testing hypothesis research done by hierarchy regression test. The result showed that profitability has a positive and significant effect on capital structure, asset structure has a negative and significant effect on capital structure, this does fit the pecking order theory. While company growth has no significant effect on capital structure. Firm size as moderator variable weakens the relationship between the asset structure to the capital structure.Key Word : pecking order theory, profitability, asset structure, growth, firm size capital structure.